Rekonstruksi Otoritas Moral Guru Melalui Pengembangan Model Mediasi Relasional BK Berbasis Ishlah - siti anisa; Muhammad Zakki Musyafa; Zamrudin Ruwais; Zalfa Zayyana; Rahmi Anekasari (Program Studi Bimbingan Konseling Pendidikan Islam Fakultas Tarbiyah Institut Agama Islam Ngawi, 2026)
he digital era has transformed interaction patterns within schools, contributing to the decline of traditional teacher authority and the increasing prevalence of relational conflicts between teachers and students. Conventional disciplinary approaches that rely on reactive and punitive measures often trigger the juridification of education and foster fear of teaching among educators. This study aims to develop a conceptual blueprint of a Relational Mediation Guidance and Counseling (GC) Model as a preventive and curative approach to addressing teacher–student conflicts. The study employed a qualitative approach using a conceptual model development design. Data were collected through digital exploratory questionnaires, in-depth interviews with guidance and counseling practitioners in Central Java, and document analysis, and were subsequently analyzed using an operational gap analysis technique. The findings indicate a tendency toward low student trust in the mediating function of guidance and counseling services, which are frequently perceived as rigid disciplinary instruments. In response to these findings, this study proposes a Blueprint of the Relational Mediation Guidance and Counseling Model that integrates Max Weber’s theory of authority, dialogical relational concepts, and the Islamic values of Adab (ethical conduct) and Ishlah (reconciliation). The proposed model consists of four main pillars: Irsyad (relational-psychological guidance), Ishlah (dialogical conflict mediation), Nashihah and Satar (confidentiality and trust enhancement), and Adab al-Virtual (digital ethics literacy). The model is expected to strengthen teachers’ moral legitimacy, enhance students’ trust in guidance and counseling services, and support the creation of a safe, inclusive, and harmonious educational environment.